Tenant-Based Hierarchical Virtual Machine Placement Policy in Cloud - Yanxia Zhou; Shuo Wang; Jun Cheng; Zhao Zhang; Jing Li (Dianxin kexue)
In the cloud ecosystem, regulating virtual machine's position can help reduce the communication cost between virtual machines and the waste of physic machine's resource. Considering the target of placement in the initialization placement,an initialization placement algorithm base on tenant was proposed. Combined the algorithm with runtime placement algorithm, the placement goal was realized. Simulation results show that the proposed algorithm reduces the number of virtual machines that need to reposition and the cost of migration.